AB0074 INTERRELATIONSHIP BETWEEN NICOTINIC ACETYLCHOLINE RECEPTOR AND CYTOKINE PRODUCTION NOTED FOLLOWING T-CELL ANTIGEN RECOGNITION AND ACTIVATION. (June 2019) - Manolios, Nicholas; Hou, Kevin; Tae, Han-Shen; Adams, David
Abstract : Background: T cells express muscarinic and nicotinic acetylcholine receptors (mAChRs, nAChRs) that increase intracellular Ca 2+ [1] on stimulation. The expression of these receptors on macrophages and their activation by vagal stimulation has recently been the focus for novel arthritis treatment [2]. Objectives: Our aim in the present study was to assess the effect of various peptides, on cytokine production and nAChRs inhibition. Methods: nAChR heterologous subunits were expressed in Xenopus oocytes and the inhibitory activity of various peptides at ACh-evoked currents were assessed. The effect of these peptides on T-cell antigen recognition and subsequent cytokine production was assessed using an antigen presentation assay (APA). Briefly, the 2B4.11 murine T cell hybridoma recognizing cytochrome c as the antigen was co-cultured with the antigen presenting B cell hybridoma line LK35.2 (I-Ek bearing) and pigeon cytochrome c in the absence or presence of peptide or several nAChRs antagonists, including mecamylamine (broad nAChR antagonist), waglerin-1 (α1β1εδ), α-bungarotoxin (α7), RgIA (α9α10), Vc1.1 (α9α10) and dihydro-β-erythroidine hydrobromide (α4β4 and α4β2). ELISA and real-time PCR were performed to measure cytokine protein levels and nAChRs T-cells mRNA express levels separately. Results: At 10μM, peptide W32052 had modest 50-55 % inhibition of human (h) α3β2 and hα4β2 nAChR subtypes, and 35% inhibition at hα9α10. W32052 greatly inhibited chimeric rat α1β1δ-mouse ε (85%) at 10μM. W32052 also inhibited IL-2, IL-6, TNF-α and GM-CSF production at 50μM in the APA. nAChRs antagonists, mecamylamine (100μM), RgIA (10nM), Vc1.1 (17.5μM) and dihydro-β-erythroidine hydrobromide (10μM) could decrease IL-2 production. However, waglerin-1 and α-bungarotoxin did not affect IL-2 production in the APA. Conclusion: W32052, an antagonist of nAChR, inhibits cytokine production following antigen recognition suggesting that there is a close link between T-cell antigen activation, ion channel regulation mediated by AChR and cytokine production. Further experiments are in progress. References: [1] Masato M, Yukari I, Takeshi FJ, et al. Acetylcholine released from T cells regulates intracellular Ca2+, IL-2 secretion and T cell proliferation through nicotinic acetylcholine receptor, Life Science, 2017, 172: 13-18. [2] Koopman FA, Chavan SS, Tak PP, et al. Vagus nerve stimulation inhibits cytokine production and attenuates disease severity in rheumatoid arthritis, PNAS, 2016, 113(29):8248-9. Disclosure of Interests: None declared